The hunt for the dawn monkey : unearthing the origins of monkeys, apes, and humans - Beard, K. Christopher (University of California Press, 2004)
Taking us back roughly 45 million years into the Eocene, "the dawn of recent life," Chris Beard, a world-renowned expert on the primate fossil record, offers a tantalizing new perspective on our deepest evolutionary roots. In a fast-paced narrative full of vivid stories from the field, he reconstructs our extended family tree, showing that the first anthropoids--the diverse and successful group that includes monkeys, apes, and humans--evolved millions of years earlier than was previously suspected and emerged in Asia rather than Africa. In The Hunt for the Dawn Monkey, Beard chronicles the saga